Auditor’s going-concern opinion prediction: the case of Slovenia - Daniel Zdolšek (Ekonomska Istraživanja, 2021)
In an audit of a firm’s financial statements, the auditor assesses whether there is material uncertainty about the firm’s ability to continue as a going concern. If the existence of material uncertainty is confirmed, the auditor considers the adequacy of the firm’s disclosures regarding its going concern in the firm’s annual report. Most commonly, if the firm’s disclosures are adequate, the auditor issues a going-concern opinion in the auditor’s report. The auditor modifies his opinion on firm’s financial statements because of auditor’s going-concern doubt on the firm’s ability to continue as a going-concern rarely in specific circumstances. In the present paper we provide an auditor’s going-concern prediction model using various combinations of a firm’s economic predictors. A sample data of 14,761 firm-year observations from Slovenia during the period 2005–2013 has been used for the model. The results reveal that firms with a going-concern qualification have a worse financial structure (i.e., lower equity financing rates), worse liquidity, worse efficiency, and worse profitability in comparison to firms without this qualification. Using a logistic regression prediction model for a going concern qualification in auditor’s report, qualification can be predicted with sufficient accuracy on a sample data of Slovenian firms.